2017
DOI: 10.1039/c6ra25793c
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled PEG–carboxymethylcellulose nanoparticles/α-cyclodextrin hydrogels for injectable and thermosensitive drug delivery

Abstract: Novel cellulose hydrogels based on the inclusion complex between a-cyclodextrin and binary-drug loaded nanoparticles (carboxymethylcellulose-betulinic acid/hydroxycamptothecine nanoparticles) were prepared in aqueous media for the first time. As the reversible supramolecular assembly behavior, the thermosensitive hydrogels showed distinctive reversible gel-sol transition properties related to structure at a particular temperature. The temperature of the gel-sol transition was decided by the concentration betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 43 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…The most commonly used thermoresponsive hydrogels are prepared from natural polymers, [141,142] proteins or polypetides, [80,143,144] pluronics, [145,146] and copolymers based on PCL, [147][148][149][150] PNIPAAM, [151][152][153][154][155][156][157] poly(d,l-lactide) (PLA), [158][159][160][161] PEG, [144,150,162] poly(amino ester urethane) (PAEU). [163,164] PNIPAAM is a widely used temperature-responsive polymer for the preparation of temperature-responsive hydrogels for controlled drug delivery applications.…”
Section: Temperature-responsive Injectable Hydrogels For Controlled Amentioning
confidence: 99%
“…The most commonly used thermoresponsive hydrogels are prepared from natural polymers, [141,142] proteins or polypetides, [80,143,144] pluronics, [145,146] and copolymers based on PCL, [147][148][149][150] PNIPAAM, [151][152][153][154][155][156][157] poly(d,l-lactide) (PLA), [158][159][160][161] PEG, [144,150,162] poly(amino ester urethane) (PAEU). [163,164] PNIPAAM is a widely used temperature-responsive polymer for the preparation of temperature-responsive hydrogels for controlled drug delivery applications.…”
Section: Temperature-responsive Injectable Hydrogels For Controlled Amentioning
confidence: 99%
“…In vivo studies showed that this hydrogel was more effective than free drugs and drug-loaded micelles. This same concept was extended while using micelles that were prepared from carboxymethylcellulose for betulinic acid/hydroxycamptothecine system delivery [184]. Similarly, Shi et al [185] prepared a tunable temperature-responsive polypseudorotaxane hydrogel based on pegylated camptothecin, an amphiphilic anticancer prodrug.…”
Section: α-Cyclodextrin/nanovehicle-based Polypseudorotaxane Hydrogelsmentioning
confidence: 99%
“…Temperature was slowly increased and sol-to-gel temperature of the nanoformulations measured upon inversion of the vials. 18 The gelling temperature range suitable for the intranasal gels is 30-34°C.…”
Section: Sol-to-gel Transition Temperaturementioning
confidence: 99%